Effectivity of fluoride treatment on hydrogen and corrosion product generation in temporal implants for different magnesium alloys. (December 2013) - Trinidad, Javier; Arruebarrena, Gurutze; Marco, Iñigo; Hurtado, Iñaki; Sáenz de Argandoña, Eneko
The increasing interest on magnesium alloys relies on their biocompatibility, bioabsorbility and especially on their mechanical properties. Due to these characteristics, magnesium alloys are becoming a promising solution to be used, as temporary implants. However, magnesium alloys must overcome their poor corrosion resistance. This article analyses the corrosion behaviour in phosphate-buffered saline solution of three commercial magnesium alloys (AZ31B, WE43 and ZM21) as well as the influence of fluoride treatment on their corrosion behaviour. It is shown that the corrosion rate of all the alloys is decreased by fluoride treatment. However, fluoride treatment affects each alloy differently.